Privileged spectatorship theatrical interventions in White supremacy - Snyder-Young, Dani 1977- (Northwestern University Press, 2020)
"Many professional theater artists attempt to use live performances in formal theater spaces to disrupt racism and create a more equitable society. Privileged Spectatorship: Theatrical Interventions in White Supremacy examines the impact of such projects, looking at how and why they do and do not intervene in white supremacy"-- Provided by publisher.